Diagnosis of laboratories of physics and chemistry in the Universidad Tecnica de Manabi - Loor, Yadira del Pilar Chavez; Cedeno, Roxana Jacqueline Panchana; Robaina, Daniel Alfonso (International research journal of management, IT and social sciences, 2017)
The following work tries to diagnose the capacities in function of the management of the maintenance of the infrastructure of the laboratories of Physics and Chemistry of the Technical University of Manabí, having as reference the external and internal relations of the processes of maintenance, for the fulfillment Of this purpose a strategic diagnosis of the Universidad Técnica de Manabí (UTM) and the identification of the critical relations of the activities of maintenance of the laboratories of Physics and Chemistry of the UTM and its evaluation of the level of integration is realized.